Equitable access to COVID-19 vaccines in Botswana: a scoping review - John T. Tlhakanelo; John T. Tlhakanelo; John Ele-Ojo Ataguba; John Ele-Ojo Ataguba; John Ele-Ojo Ataguba; John Ele-Ojo Ataguba; Vincent Pagiwa; Nankie Ramabu; Khutsafalo Kadimo; Dintle Molosiwa; Grace Njeri Muriithi; Daniel Malik Achala; et al. (Frontiers in Health Services, 2025)
IntroductionDespite global market complexities, Botswana acquired about 2.6 million COVID-19 vaccine doses between March 2021 and March 2022, 76% of which were purchased while 24% were donations. Thus, the study was envisaged to aggregate evidence on the case of Botswana's COVID-19 vaccine access patterns, hesitancy, and uptake.Materials and methodsWe conducted a scoping reviewof Botswana-based articles using a predetermined search strategy to search databases including Medline, CINAHL, Web of Science, PubMed, Scopus, and Google Scholar. The review included all the English-language written peer-reviewed and grey literature reporting on vaccination in Botswana, to broaden coverage in recognition of limited publications on COVID-19 vaccinartion in Botswana. Non-English articles were excluded due to limited translation resources. Due to the heterogeneity of studies, a narrative synthesis approach was used to collect, synthesize, and map the literature.ResultsAs of 31 December 2021, 80.6% of the Botswana national target of 1,390,856 people over 18 years had received at least one dose of a COVID-19 vaccine, while 71.9% were fully vaccinated. Various vaccine distribution channels were utilized, including public facilities and outreaches, to improve access and uptake of vaccines. COVID-19 vaccine acceptance was considered generally high (73.4% amongst adults), and found positively associated with the male gender, those with comorbidities, those with non-restrictive religious beliefs, and those aged 55–64 years who thought the vaccine was safe for use. COVID-19 vaccine delivery relied on existing Expanded Program on Immunization (EPI) structures and therefore experienced to existing EPI challenges including, lack of transport, shortage of human resources, and vaccine stock-outs.ConclusionsUnder-performance of immunization programs at the district level, characterized by declining immunization coverage and inadequate outreach services, exacerbates disparities in vaccine access. Efforts to strengthen healthcare infrastructure and expand outreach services are essential for reaching populations with limited access to healthcare facilities, particularly in rural and hard-to-reach areas. Collaboration with other government entities and the private sector improved vaccine access.